Giant hyperplastic gastric polyp: A diagnostic dilemma!! - Ashish Jain; Dimple Chaudhary; Surbhi Goyal; Anil K Agarwal; Puja Sakhuja (Wolters Kluwer Medknow Publications, 2022)
Gastric hyperplastic polyps (GHP) account for a majority of benign gastric polyps. Most of the GHPs are <2 cm, asymptomatic, and incidentally detected on endoscopy or radiologically. With increasing size, these polyps manifest as upper gastrointestinal bleeding, iron deficiency anemia, and gastric outlet obstruction (GOO). We report an unusual case of giant GHP simulating gastric carcinoma and posing as a diagnostic challenge for the surgeons emphasizing the diagnostic role of histopathology. A 46-year-old female presented with clinical features of progressive GOO for 1 year. Endoscopy revealed an eccentric proliferative lesion in the antrum. Computed tomography showed a polypoidal, enhancing mural thickening involving distal body and antro-pyloric region measuring 8.4 cm × 6.6 cm × 1.8 cm. Subtotal gastrectomy was done in view of clinical features of GOO and having a clinical suspicion of malignancy. Gross examination showed a giant sessile hyperplastic polyp with lobulated surface. Microscopy revealed features of a large, sessile hyperplastic polyp without any evidence of dysplasia. The patient was symptomatically relieved and is on follow-up. To conclude, giant GHPs can mimic gastric carcinoma on endoscopy and radiology. The possibility of giant GHP should be kept in mind in the presence of an intensely contrast-enhancing polypoidal lesion in the gastric antrum. Long-term endoscopic follow-up is recommended.